Molecular characterization of corneal ulcers causing Staphylococcus aureus - Jain, Deepika N.; Kamble, Vilas A. (International Journal of Research in Medical Sciences, 2017)
Background: The human eye is one of the most remarkable sensory systems. Human beings gather most of the information about the external environment through their eyes and thus rely on sight more than on any other sense, with the eye being the most sensitive organ we have. Molecular characterization of Staphylococcus aureus from the cases of corneal ulcers. Methods: A total of 300 samples of corneal ulcers collected from various ophthalmology hospitals, government hospital and clinical laboratories of different places of Maharashtra, India. The Isolates were identified based on the colony morphology and biochemical reaction. The isolates were subjected for antibiotic sensitivity test and perform its molecular characterization. Results: In present study, 39 coagulase positive Staphylococcus aureus, pathogenic bacteria isolated from corneal ulcers. Conclusions: Staphylococcus aureus is one of the most significant pathogens in bacterial keratitis. Early diagnosis and prompt treatment are needed to minimize the possibility of permanent vision loss and reduce structural damage to the cornea.